Unlocking arteriovenous fistula success: a prospective randomized controlled trial on intraoperative IV heparin for superior vascular access outcomes - Rajawat, Mahatab Singh; V., Shivakumar; R., Keshavamurthy (International Surgery Journal, 2025)
Introduction: End-stage renal disease (ESRD) prevalence is rising globally, making vascular access for haemodialysis increasingly important. Arteriovenous fistula (AVF) remains the gold standard for durable vascular access, but early failure due to thrombosis remains a concern. The use of intraoperative heparin to improve patency is debated. To assess the effect of a single intraoperative intravenous dose of heparin on early AVF patency and postoperative complications. Methods: This prospective randomized controlled trial was conducted from January to December 2019 at the Institute of Nephrourology, Bangalore. A total of 240 patients undergoing AVF creation were randomized into two groups: Group A received 5000 IU IV heparin intraoperatively (n=130) and Group B underwent surgery without heparin (n=110). Primary outcome was AVF patency on postoperative days 1 and 8. Secondary outcomes included postoperative bleeding, hematoma, infection, and thrombosis. Statistical significance was set at p<0.05. Results: Baseline characteristics and AVF type distribution were comparable between groups. On day 1, RCAVF patency was significantly higher in the heparin group (96.5% vs. 84.2%, p=0.01). On day 8, RCAVF patency remained higher in the heparin group (94.4% vs. 80.2%, p=0.007). BCAVF patency improvement was not statistically significant. Complication rates did not differ significantly. Conclusions: A single dose of intraoperative IV heparin significantly lowers thrombosis rates and enhances patency in both radiocephalic and brachiocephalic AVFs. Notably, the improvement reached statistical significance in radiocephalic fistulas, highlighting its potential as a simple yet powerful intervention especially in AVFs with small-caliber vessels.